Clinical evolution, transfusion reactions, and transfusion safety in recipients of blood components from donors with positive serology and/or positive PCR results for SARS-CoV-2 - Brito Silva Bulhões, Moniky; Martins Schweinberger, Bruna; Rodrigues Cohen, Carolina; Vaccari Batista, Carolina; Machado Arlindo de Mattos, Elissandra; Bonacina, Francine; Giron Correa, Gabriel; Pasqualim, Gabriela; Risczik Arruda Corrêa, Janaína Aparecida; Barboza Cardoso, João Vitor; et al. (Clinical and Biomedical Research, 2026)
Introduction: The COVID-19 pandemic has raised concerns about the possibility of virus transmission via blood transfusions. Objective: This study aimed to verify the safety of transfusing blood components from donors with positive SARS-CoV-2 serology and/or detectable PCR in serum. Methods: An analytical, longitudinal, and retrospective cohort study was conducted using 208 serum samples from blood donations collected from January to March 2021 at a Brazilian blood bank. After initial screening with a rapid test, samples were divided into a Test Group (TG), with 98 samples positive for SARS-CoV-2, and a Control Group (CG), with 110 negative samples. We collected donor demographic data, tracked blood components, and evaluated recipients regarding their demographic profile, hospitalization data, transfusion reactions, and SARS-CoV-2 test results up to 28 days after transfusion. Results: In the TG, 50% of samples were IgM positive and 97% were IgG positive. In total, 381 blood components were transfused in 217 transfusion procedures to 124 recipients. The recipients had a mean age of 43.4 years, with 49.2% in clinical beds and a median hospital stay of 28 days. The frequency of transfusion reactions was 2.3%, and 16.9% of cases presented with dyspnea/desaturation, with no significant difference between groups. Conclusion: In conclusion, we found no differences in transfusion outcomes between groups, as well as no evidence of transfusion-transmitted SARS-CoV-2 cases.